Analysis of the occupational performance in women victims of domestic violence (Research, Society and Development, 2020)
Introduction: Domestic violence has received a prominent place among health professionals because it is considered a public health problem, as women in this situation alters their occupational performance. Objectives: To analyze the role of Occupational Therapy in the face of changes in the occupational performance of women who suffer domestic violence. Methodology: The method chosen in this investigation was cartographic. The context was held at the Nilopolitana Woman's House in the State of Rio de Janeiro, where they were located. The strategy for data production involved collective meetings with 25 women over 18 years of age, for data collection, using verbalizations in occupational therapeutic workshops, field diaries, tests and interviews. The software IRAMUTEQ, which made possible several types of analysis of the textual data, organizing them by the distribution and quantification of the vocabularies, analyzed the data. Results: 293 registration units were produced. It stands out: husband, home, body and son, which linked to occupational performance, generated the categories ADL, IADL, body and subjectivity. Conclusion: Domestic violence from the Occupational Therapy identified that this profession attenuates and contributes to welcoming, health promotion, self-perception, and opens a new field of action for this profession.